Comparison of Pain Control and Inflammatory Profile in Cesarean Section Patients Treated with Multimodal Analgesia Utilizing Paracetamol and Ibuprofen - Gaus, Syafruddin; Afif, Yudhitya; Ala, Alamsyah Ambo; Tanra, Andi Husni; Ratnawati, Ratnawati; Rum, Muhammad (Open Access Macedonian Journal of Medical Sciences, 2023)
AIM: This single-blind study aimed to compare the combination of paracetamol with various doses of ibuprofen as multimodal analgesia in C-section surgery patients under spinal anesthesia. Levels of interleukin (IL)-6 and C-reactive protein (CRP) were analyzed as markers of inflammation. METHODS: Treatment groups (20 patients each) were: Group A, 750 mg paracetamol and 400 mg ibuprofen; Group B, 750 mg paracetamol and 600 mg ibuprofen; and Group C, 750 mg paracetamol and 800 mg ibuprofen. Degree of pain (movement and rest), scored using the numeric rating scale (NRS) and levels of IL-6 and CRP were assessed at various time points within 24 h of surgery. Side effects and numbers of subjects requiring rescue fentanyl administration were also recorded. RESULTS: Group C showed a rest NRS score of 1.00 ± 0.00 6 h postoperatively, compared with 2.00 ± 0.00 in Group B and 2.35 ± 0.87 in Group A. 4 h postoperatively, movement NRS scores were 1.00 ± 0.00 for Group C, compared to 3.00 ± 1.77 for Group B, and 4.85 ± 1.81 for Group A. At 12 h, IL-6 levels hours were 2.66 ± 0.04 pg/mL for Group A, 2.39 ± 0.02 pg/mL for Group B, and 2.05 ± 0.01 pg/mL for Group C. At 6 h, CRP levels were 1.18 ± 0.04 mg/L for Group A, 0.95 ± 0.01 mg/L for Group B, and 0.70 ± 0.02 mg/L for Group C. Overall, Group C showed the lowest values for all parameters analyzed, compared with other groups, and the differences were significant (p < 0.05). In addition, none of the patients in Group C required rescue fentanyl (p < 0.05), and no patients in any of the groups showed any side effects. CONCLUSION: For pain management after C-section surgery, the combination of 750 mg paracetamol and 800 mg ibuprofen yielded the best results as assessed by NRS scores, levels of IL-6 and CRP, and fentanyl rescue.